Is There a Relationship Between the Functional Movement Screen, Star Excursion Balance Test, and Balance Error Scoring System?. Issue 4 (July 2018) - Harshbarger, Nicole D.; Anderson, Barton E.; Lam, Kenneth C.
Abstract : Objective: To evaluate associations between the Functional Movement Screen (FMS), Star Excursion Balance Test (SEBT), and Balance Error Scoring System (BESS) scores. Design: Correlational. Setting: College athletic training facilities. Participants: Fifty-two intercollegiate athletes (men = 36 and women = 16) representing 8 sports and cleared for unrestricted sport participation. Interventions: Participants completed the FMS, SEBT, and BESS, in random order, during 1 testing session. Testing order was randomized to control for fatigue and learning effects. Main Outcome Measures: Composite and item scores for the FMS, SEBT, and BESS. Results: A fair, negative correlation was found between FMS asymmetry and SEBT composite (r = −0.31, P = 0.03) scores. Fair, positive correlations were reported for FMS rotary stability task and SEBT anterior (r = 0.37-0.41, P ⩽ 0.007) and posteromedial (r = 0.31, P = 0.03) reaches. Fair, negative correlations were reported for FMS deep squat and BESS single-leg firm (r = −0.33, P = 0.02), double-leg foam (r = −0.34, P = 0.02) and tandem foam (r = −0.40, P = 0.003), FMS inline lunge and BESS single-leg firm (r = −0.39, P = 0.004), FMS trunk stability pushup and tandem foam (r = −0.31, P = 0.025), and FMS composite and BESS single-leg firm (r = −0.37, P = 0.007). Little-to-no correlations were reported for remaining comparisons. Conclusions: Results indicate that each instrument provides distinct information about function, with only small areas of overlap. Associations between the FMS asymmetry score and SEBT composite score may indicate a relationship between movement asymmetry and postural stability. Associations between the FMS deep squat and BESS foam tasks may be related to underlying neuromuscular control factors.